ANALISIS KESALAHAN DALAM MENULIS KARANGAN FIKSI SISWA KELAS V SEKOLAH DASAR 38 SUNGAI AMBAWANG - Ambar Anggar Ningrum; Hery Kresnadi; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to analyze errors in writing fiction essays for fifth grade students at 38 Sungai Ambawang Elementary School. The research method uses a descriptive method with a qualitative research form. The participants of this study acted as data sources, namely the 11 students of class V Elementary School 38 Sungai Ambawang. The research instrument is the researcher himself. Data collection techniques used are documentation techniques and reading & note- taking techniques. The data analysis technique uses the Miles and Huberman model which includes four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that there were 299 writing errors from 11 students' essays. Writing errors are divided into 25 errors of word choice (diction), or 8.36%, 244 errors or 81.60% of word writing (spelling) errors, and 30 errors of writing effective sentences or 10.30%.